UNFORGETTABLE PAUL DOBRYANSKY - Horob, M. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In a review the just given out is analyzed in the Ivano-Frankivs’k book "Eternal Paul: Flashbacks. Interview. Leaves".